Approaches to ethics for public administrators / Asmidar Lokman and Ahmad Tarmizi Talib - Lokman, Asmidar; Talib, Ahmad Tarmizi (Universiti Teknologi MARA, Shah Alam, 2016)
Ethics essential existence in Public Administration is described as the soul of public administration. Public services around the globe have increasingly placed ethics as the basis of actions in its administrations. Scholars emphasized on the promotion of ethical practice in the public service to support the ethical practitioners. With the public administrators are increasingly playing a key role in making and implementing policies hence there are high expectations on them to act with a higher moral character. This means that they will have to constantly obey stricter ethical standards. However, scandalous activities of some public administrators have placed the public service under intense public spotlight and opened to relentless criticisms by the media. The adage of 'living in a goldfish bowl' illustrates the pressure to conform ethically. Accordingly, this paper seeks to highlight some approaches relevant to the role that can be expected off a public administrator to practice.